Epidemiology of breast cancer: retrospective study in the Central African Republic. (December 2016) - Balekouzou, Augustin; Yin, Ping; Pamatika, Christian; Bishwajit, Ghose; Nambei, Sylvain; Djeintote, Marceline; Ouansaba, Barbara; Shu, Chang; Yin, Minghui; Fu, Zhen; Qing, Tingting; Yan, Mingming; et al.
Abstract Background Breast cancer is recognised as a major public health problem in developing countries; however, there is very limited evidence about its epidemiology in the Central African Republic. The aim of this study was to investigate the epidemiological and histopathological characteristics of breast cancer in Bangui. Methods This is a retrospective study based on the data collected from pathological anatomy records from 2003 to 2015 in Bangui. A questionnaire was designed to collect information and data was analysed using descriptive and inferential statistical methods. Results The mean age was 45.83 (SD = 13.5) years. The age group of 45–54 years represented the majority of the study population (29.3%). Over 69.5% of the women were housewives with a moderate economic status (56.9%). Less than 14% of the study population had a level of academic degree and 85.6% lived in cities. The breast cancer prevalence was 15.27%. The age-standardized incidence and death by world population (ASW) were 11.19/100, 000 and 9.97/100, 000 respectively. 50–54 years were most affected. Left breast cancer is mainly common and the time between first symptoms and consultation is more than 48 months. Most (69%) of the samples analysed were lumpectomy. The most common morphology of breast cancer was invasive ductal carcinoma (64.9%). Scarff Bloom Richardson III was the main grade in both common pathological types, but their proportion showed no significant increase along with time (χ 2 = 7.06, p  = 0.54). Invasion of regional lymph node differed significantly among the pathological type of breast cancer (χ 2 = 24.6, p  = 0.02). Surgery and chemotherapy were appropriate treatment yet 84.5% of the cases died. Conclusion The findings of this study showed that breast cancer is common and mostly affected women. Epidemiological trends are more or less common to those of developing countries with a predominance of invasive ductal carcinoma. However, most of the women studied live in an urban area and developed the disease in advanced stage. The establishment of an appropriate framework will effectively contribute to promoting the early detection and reducing the incidence of this disease in the population.